2017
DOI: 10.1128/jvi.02241-16
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-Specific Evolution of Hepatitis E Virus

Abstract: Hepatitis E virus (HEV) is the most common cause of acute viral hepatitis globally. HEV comprises four genotypes with different geographic distributions and host ranges. We utilize this natural case-control study for investigating the evolution of zoonotic viruses compared to single-host viruses, using 244 near-full-length HEV genomes. Genome-wide estimates of the ratio of nonsynonymous to synonymous evolutionary changes (dN/dS ratio) located a region of overlapping reading frames, which is subject to positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 94 publications
2
21
0
Order By: Relevance
“…Across NUH patient sequences, two protein regions were highly conserved, similar to a previous analysis of global HEV‐3 genotypes . The first region in ORF1 between aa residues 250‐450 covers the entire Y domain (aa241‐442), a sequence highly similar to the Rubella virus, and critical to HEV infectivity .…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Across NUH patient sequences, two protein regions were highly conserved, similar to a previous analysis of global HEV‐3 genotypes . The first region in ORF1 between aa residues 250‐450 covers the entire Y domain (aa241‐442), a sequence highly similar to the Rubella virus, and critical to HEV infectivity .…”
Section: Discussionsupporting
confidence: 73%
“…Across NUH patient sequences, two protein regions were highly conserved, similar to a previous analysis of global HEV-3 genotypes. 40 The first region in ORF1 between aa residues 250-450 covers the entire Y domain (aa241-442), a sequence highly similar to the Rubella virus, 3 and critical to HEV infectivity. 41 The second conserved region in ORF2 between aa residues 120-400 cover the entire S domain (aa130-319) and half of the M domain (aa320-456).…”
Section: Consensus Aa Changesmentioning
confidence: 99%
“…I thus chose an approach focused, at first instance, on the evaluation of the amino acid diversity of homologous overlapping proteins, which is the final result of the complex pattern of the interdependent nucleotide substitutions that occur in dual-coding regions. Unlike previous studies, limited to a few virus species (Sabath et al, 2012;Zaaijer et al, 2007;Liang et al, 2010;Shukla and Hilgenfeld, 2015;Brayne et al, 2017), I examined a large dataset of 75 overlaps from 59 virus species.…”
Section: Discussionmentioning
confidence: 99%
“…Recombination between strains infecting different host species can have serious implications for HEV evolution and inter‐species transmission. It has been suggested that the overall distribution of different HEV genotypes is due to the fact that different clades of the virus interact with different hosts, which could impose differential selective pressures on the pathogen as a part of host–pathogen interactions (Brayne, Dearlove, Lester, Kosakovsky Pond, & Frost, ). Moreover, the analysis of mutations in the viral genome suggests that HEV is under substantial evolutionary pressure to develop mutations enabling evasion of the host immune response and resistance to antiviral treatment (Ikram et al., ).…”
Section: Discussionmentioning
confidence: 99%